2019
DOI: 10.3390/nu11122866
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of n-3 PUFA Binding Phosphatidylglycerol on Metabolic Syndrome-Related Parameters and n-3 PUFA Accretion in Diabetic/Obese KK-Ay Mice

Abstract: n-3 Polyunsaturated fatty acid binding phospholipids (n-3 PUFA-PLs) are known to be potent carriers of n-3 PUFAs and provide health benefits. We previously prepared n-3 PUFA binding phosphatidylglycerol (n-3 PUFA-PG) by phospholipase D-mediated transphosphatidylation. Because PG has excellent emulsifiability, n-3 PUFA-PG is expected to work as a functional molecule with properties of both PG and n-3 PUFAs. In the present study, the health benefits and tissue accretion of dietary n-3 PUFA-PG were examined in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Although our gas chromatographic analysis detected a total of 19 fatty acids in the brain, the fatty acid profile of the brain was different from that of other tissues. One notable difference was the large amount of docosahexaenoic acid in both phytol‐fed and control mouse brains (7.3 and 7.9 mg/g, respectively), compared to the low values in adipose tissue (Table 3) and liver (Table 4), similar to previous reports (Chen, Takatani, Beppu, Miyashita, & Hosokawa, 2019). Table 5 shows fatty acids whose contents in the brain were different between groups.…”
Section: Resultssupporting
confidence: 87%
“…Although our gas chromatographic analysis detected a total of 19 fatty acids in the brain, the fatty acid profile of the brain was different from that of other tissues. One notable difference was the large amount of docosahexaenoic acid in both phytol‐fed and control mouse brains (7.3 and 7.9 mg/g, respectively), compared to the low values in adipose tissue (Table 3) and liver (Table 4), similar to previous reports (Chen, Takatani, Beppu, Miyashita, & Hosokawa, 2019). Table 5 shows fatty acids whose contents in the brain were different between groups.…”
Section: Resultssupporting
confidence: 87%
“…In fact, there are several studies has been reported the superiority of n-3 PUFA-phospholipids in alleviating obesity-related disorders compared to other lipid forms, such as triacylglycerol, and ethyl esters. [27][28][29] Similarly, we found here that mice supplemented with EPA-PC had lower body weight gain and perirenal WAT weight than EPA-EE. Most surprisingly, EPA-PlsEtn administration completely reversed body weight gain in obese mice, which was even better than the regular-chow diettreated group.…”
Section: Discussionsupporting
confidence: 83%
“…KKay mice are spontaneous diabetic and obese models that are good for studying the metabolism-related diseases ( 21 , 22 ). As early as 1988, some scholars have found that the effect of thermogenesis in brown fat is involved in obese KKay mice ( 23 ).…”
Section: Discussionmentioning
confidence: 99%